Genetic diversity studies in relation to seed yield and its component traits in Indian mustard (Brassica juncea L. Czern & Coss.) - Dhiraj Singh; Rajesh Kumar Arya; Navin Chandra; Ram Niwas; Phillip Salisbury (Journal of Oilseed Brassica, 2026)
A collection of 33 genotypes of [Brassica juncea (L) Czern & Coss.] (12 from Australia, 21 from India)was grown in randomized block design. Seed yield, 1000 seed weight, number of secondary branches,number of seed per siliquae, siliqua length, number of primary branches, plant height and number of siliqueon main raceme were the maximum contributors for genetic diversity among the genotypes. Cluster I and IXincluded maximum six genotypes each and cluster IV was having only one genotype (JM-016). Maximumdivergence was observed between clusters IV and VIII (8.3) followed by cluster IV and VI (7.1), clusterIV and V (7.1) and cluster V and VIII (6.9). The genotypes JM016, PCR 7 and RH 8812 were observed asmost divergent. The genotypes from cluster V had short stature, earliest in days to 50 per cent flowering andin maturity and cluster VIII had highest siliqua length, number of seed per siliqua, 1000 seed weight andseed yield (kg/ha) along with high value of number of primary and secondary branches, main raceme lengthand oil content. The cluster V and VIII were among the most divergent clusters having high seed yieldperformance along with its contributing traits and high in oil content. The probability of getting better segregantsand promising recombinants is expected to be more, in case the genotypes of these clusters will be used inthe hybridization programme.